Peran dan Upaya Pemerintah terhadap Kepatuhan Wajib Pajak - Astrid Calista Saraswati Sejahtera; Nouval Dwi Bhara Daksa; Dean Power Saragih; Nanjelina Adinda Fazya; Dimas Herdian Nugrahimsyah (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
Tax is one of the main sources of state income. We already know that taxpayer compliance is required to fulfill the tax itself. Then, to maintain a balanced level of taxpayer compliance in paying taxes, the government's role is needed to guarantee legal certainty so that it can fulfill other aspects such as expediency and justice. This is where the role of the government can be seen from the efforts taken to fulfill this. The purpose of this article is to answer and understand the role and efforts of the government towards taxpayer compliance. This article was prepared using a descriptive study and that is the study method through norms, applicable laws and regulations, journals or other sources. Apart from being descriptive, this article was prepared using searches through document and literature studies.